Non‐operating risk and cash holdings: Evidence from pension risk - Almaghrabi, Khadija S. (Journal of Banking & Finance, 2023)
Using a large sample of U.S. firms sponsoring defined benefit (DB) plans, we examine the impact of pension risk on firms’ cash management decisions. We document a positive curvilinear relationship between pension risk and cash holdings, finding that cash holdings by firms with high pension risk dramatically increase as their pension risk increases. However, this relationship appears only in the case of financially unconstrained firms, which suggests that the incentives to hedge against pension risk are only relevant when such risk is manageable. These results hold across different specifications, as well as when using several tests to address the potential endogeneity issue. We conduct multiple tests to examine alternative explanations of the findings, and we find that our results are mainly explained by the hedging incentives against pension risk and that the excess cash held by firms with higher pension risk is realized in a higher marginal value of cash.